Relationship Between Artificial Intelligence Use and Writing Anxiety: in English Writing Tasks - Sabrina Decriz Elvandintha; Susiati Susiati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
Artificial Intelligence (AI) is now becoming a technology increasingly integrated into student’s academic writing practices, particularly in English writing tasks. AI offers the convenience of assisting students with real-time feedback, but its use also has the potential to impact affective aspects, such as writing anxiety. With its increasingly widespread use, it is important to conduct a study to understand how students utilize AI in English writing tasks and to examine the relationship between the use of AI and student's writing anxiety. This study used a quantitative approach, collecting data from 106 Department of English Education student at Muhammadiyah University of Surakarta as respondents through a Likert-scale questionnaire and regression analysis using SPSS. The results of the study indicate that students use AI in a high frequently for various purposes. Furthermore, a positive relationship was found between the use of AI and writing anxiety, although the strength of the relationship was weak. These findings suggest a correlation, but cannot be interpreted as a direct cause-and-effect relationship. It is crucial for educators to utilize and guide the use of AI in a more structured manner in learning and encourage further research related to the deeper exploration of student’s affective aspects.